Age-Related Differences for Cardiorespiratory Fitness Improvement in Patients Undergoing Cardiac Rehabilitation - Taylor, Jenna L.; Medina-Inojosa, Jose R.; Chacin-Suarez, Audry; Smith, Joshua R.; Squires, Ray W.; Thomas, Randal J.; Johnson, Bruce D.; Olson, Thomas P.; Bonikowske, Amanda R. (Frontiers in Cardiovascular Medicine, 2022)
Objective: We investigated age-related differences for peak VO2 improvement with exercise training during CR. Patients and Methods: This was a retrospective cohort study of the Mayo Clinic Rochester CR program including adult patients who attended CR (≥1 session) for any eligible indication between 1999-2017 and who had a cardiopulmonary exercise test pre and post CR with VO2 data (peak respiratory exchange ratio ≥1.0). Younger (20-49yrs), midlife (50-64yrs), and older adults (≥65yrs) were compared using ANOVA for delta and percent change in peak VO2; and percentage of peak VO2 responders (>0% change). Results: 708 patients (age:60.8±12.1 years; 24% female) met inclusion criteria. Delta and percent change in peak VO2 was lower for older adults (1.6±3.2mL.kg.min-1; 12±27%) compared with younger (3.7±4.0mL.kg.min-1, p<.001; 23±28%, p=.002) and midlife adults (2.8±3.8mL.kg.min-1, p<.001; 17±28%, p=.04). For midlife, delta change, but not percent change in peak VO2 was significantly lower (p=.02) compared with younger. Percentage of responders was only different between older and younger (72% vs 86%; p=.008). Sensitivity analyses in non-surgical patients showed similar differences for delta change, and differences in percent change remained significant between older and younger adults (10±20% vs 16±18%; p=.04). Conclusions: In CR patients, older adults had lower improvement in cardiorespiratory fitness than younger and midlife adults. While excluding surgical patients reduced age-related differences, older adults still had lower cardiorespiratory fitness improvement during CR. These findings may have implications for individualizing CR programming in aging populations to reduce future cardiovascular risk.